Youth and Laws of Success – Pakistan’s Context - Rahman, Shafiq ur; Tahir, Muhammad; Wattoo, Omar Mahmood; Shahid, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This article aims to identify measures to harness Pakistan's youth bulge as a valuable asset for national prosperity by emphasizing their critical role in the country's development. Pakistan's total population stands at 241.49 million, with approximately 64% of the population being below the age of 30, presenting both opportunities and challenges. To transform this youth demographic into a dividend rather than a threat, it highlights three potential sources: religion, Iqbal's poetry, and mind sciences, which can help harness their potential for the nation. Drawing from case studies of recently developed Asian countries that have effectively leveraged their youth, the article includes relevant data of Japan, Singapore South Korea and China to streamline the study. For transforming process, the article proposes dividing the youth into three age groups (below 7 years, 7-14 years, and 15-30 years) and suggests tailored measures for each. In the end it recommends a set of measures.